Re-Establishing Human-Nature Relations: Responses of Indigenous People of Indonesia to Covid-19 - Maarif, Samsul (Interdisciplinary journal for religion and transformation in contemporary society, 2021)
Indigenous peoples of the world, including those of Indonesia, were more potentially at risk for Covid-19, due to their being marginalized and thus their lack of access to necessary information resources. Despite being marginalized and vulnerably impacted by the pandemic, indigenous people of Indonesia had re-contextualized their indigenous strategies that enabled them to survive and even offer lessons worth considering: indigenous ecocentrism. Data on their ideas and responses to the pandemic were collected through weekly webinars, featuring representatives of indigenous people as the main speakers, personal calls, and supported by a series of fieldwork, including data on the situation before the pandemic. Their responses to the pandemic were commonly based on ecocentrism; that Covid-19 was an ecological disaster caused by human’s misconducts against humanity and human-nature relations. In response, they took responsibilities to perform eco-centric rituals, and called for a re-establishment of ecological human-nature relations to deal with Covid-19.